Age diversity in teams: Examining the impact of the least agreeable member - Luksyte, A.; Avery, D.R.; Parker, Sharon; Wang, Y.; Johnson, L.U.; Crepeau, L. (WILEY, 2022)
Our research examined how team age diversity can be either detrimental or beneficial for team performance depending on team agreeableness minimum. In age diverse teams, a disagreeable teammate may trigger age-based stereotypes about his/her social group, thereby activating social categorization. This would result in decreased relational team functioning and worsened team performance. When the least agreeable member scores high on agreeableness, negative social categorization processes may not be triggered in age diverse teams. They may focus on informational diversity with beneficial effects for team relational processes and team performance. We tested our model in three samples (Study 1: k = 81, N = 254; Study 2: k = 109, N = 434; Study 3: k = 195, N = 1784) wherein performance was measured both objectively (Studies 1 and 2) and subjectively (Study 3). In both Studies 1 and 2, team age diversity was positively related to team performance when team agreeableness minimum was high. In Study 2, when the least agreeable person scored low on agreeableness, greater age diversity resulted in lower performance, and this relationship was mediated by higher interpersonal conflict. In Study 3, these interactive effects transpire via reduced team cohesion—another aspect of relational team functioning.